High CRI white light-emitting phosphor-in-glass film for laser lighting applications by adding cyan phosphor BaSi2O2N2:Eu2+. Issue 5 (1st March 2023) - Zeng, Yi; Guo, Fan; Rao, Guang-Hui; Zhao, Jing-Tai; Zhang, Zhi-Jun
Abstract: PiGF (Phosphor-in-glass film) with high color rendering was successfully prepared at a low sintering temperature. The influence of sintering temperature, the mass ratio of glass and phosphor, and different fluorescent layers on the luminescence properties of PiGF was systematically studied. It is of note that the "cyan cavity" is significantly reduced due to the addition of "cyan phosphor" (BaSi2 O2 N2 :Eu 2+ ). Under 455 nm blue light laser excitation, PiGF has the highest luminous efficiency of 94.55 lm/W and a white light composite PiGF with a correlated color temperature of 5500 K and a color rendering index of 95 can be obtained. In short, this work shows that the PiGF has great potential application in white light laser lighting. Highlights: The PiGF has a very high color rendering index, which can reach 95. While maintaining a high color rendering index, the correlated color temperature is low, only about 5500 K. First application of cyan phosphor (BaSi2 O2 N2 :Eu 2+ ) to laser lighting to fill in cyan glow.